2013
DOI: 10.3945/ajcn.112.036418
|View full text |Cite
|
Sign up to set email alerts
|

Management of protein-energy wasting in non-dialysis-dependent chronic kidney disease: reconciling low protein intake with nutritional therapy

Abstract: Protein-energy wasting (PEW), characterized by a decline in body protein mass and energy reserves, including muscle and fat wasting and visceral protein pool contraction, is an underappreciated condition in early to moderate stages of chronic kidney disease (CKD) and a strong predictor of adverse outcomes. The prevalence of PEW in early to moderate CKD is $20-25% and increases as CKD progresses, in part because of activation of proinflammatory cytokines combined with superimposed hypercatabolic states and decl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
205
0
14

Year Published

2013
2013
2022
2022

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 236 publications
(222 citation statements)
references
References 116 publications
3
205
0
14
Order By: Relevance
“…The applicability of many nutritional interventions and their effects on outcomes in patients with moderate to advanced CKD, including those with protein‐energy wasting or at high risk of its development, has not been well studied. The challenge remains as to how to reconcile low dietary protein intake—to avoid or delay dialysis initiation—with adequate nutrient intake and nutritional therapy while insuring favourable nutritional status and to avoid or correct protein‐energy wasting 13. The field lacks an up‐to‐date systematic review and meta‐analysis study on the subject with a focus on the conservative management of CKD.…”
Section: Introductionmentioning
confidence: 99%
“…The applicability of many nutritional interventions and their effects on outcomes in patients with moderate to advanced CKD, including those with protein‐energy wasting or at high risk of its development, has not been well studied. The challenge remains as to how to reconcile low dietary protein intake—to avoid or delay dialysis initiation—with adequate nutrient intake and nutritional therapy while insuring favourable nutritional status and to avoid or correct protein‐energy wasting 13. The field lacks an up‐to‐date systematic review and meta‐analysis study on the subject with a focus on the conservative management of CKD.…”
Section: Introductionmentioning
confidence: 99%
“…9 Inadequate protein intake and loss of nutrients are major causes of malnutrition. 10 We evaluated the impact of nutritional status and intestinal function on the incidence of peritonitis in patients with CAPD, and compared the nutrition and inflammatory parameters between the peritonitis group and the non-peritonitis group during the same period. We found that erythrocyte sedimentation rates and C-reaction protein levels were significantly elevated and serum albumin levels were significantly reduced in the peritonitis group compared with the non-peritonitis group, and no significant differences in hemoglobin levels between the peritonitis and non-peritonitis groups.…”
Section: Discussionmentioning
confidence: 99%
“…Protein energy wasting occurs in the early and middle stages of CKD, and is characterized by loss of muscle and fat tissue, and a decrease in body protein mass and energy reserve (1). According to studies performed in numerous countries, metabolic imbalance and abnormal energy expenditure varies (18%-80%) in CKD patients according to the stage of disease (2).…”
Section: Introductionmentioning
confidence: 99%